Comparison Analysis of Baptist and Lutheran Christian Teachings on Salvation Based on the Study of the Text of Mark 16:16 - Djone Georges Nicolas; Jannes Eduard Sirait; Titin; Idaman Zega (Jurnal Multidisiplin Madani, 2023)
Baptist and Lutheran are Christian teachings that have developed to date. Mark 16:16 is one of the Bible verses that is often used to understand the fandango of salvation in Christianity. In this research, a comparison and analysis of Baptist and Lutheran Christian interpretations of this chapter are carried out, and how this influences their view of salvation. This research will discuss how Baptist and Lutheran Christian teachings integrate Mark 16:16 into their teachings about salvation by discussing Baptist Christian teachings of understanding salvation through sanctification and Lutheran teachings of understanding salvation through faith. This study also discusses how these teachings influence the views of each teaching about sin, repentance, and the hope of salvation. By using qualitative methods with objective analysis and legitimate sources, the implications of the differences between Baptist and Lutheran Christian teachings are identified for society. This study discusses the differences in these teachings that affect relations between religions and tolerance for differences. The purpose of this research is to help readers understand the differences between Baptist and Lutheran Christian teachings and how this affects their views of salvation. It is hoped that this research can help readers understand differences in teachings and promote understanding and tolerance among Christian theologies. Therefore, this research contributes to the development of Christian theology and inter-religious discussion